A procedure to detect 6 basic STSs and 11 extended STSs in the AZF region using multiplex PCR - Thi Lan Anh Luong; Thu Lan Hoang; Minh Ngoc Nguyen; Ngoc Dung Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
Microdeletions of Y chromosomes frequently occur in 3 subregions of the AZF, namely, AZFa, AZFb, and AZFc, with 6 basic STS marker sequences, which are sY84, sY86 (AZFa), sY127, sY134 (AZFb), and sY254, sY255 (AZFc). According to EAA/EMNQ guidelines, 11 additional AZFabc marker sequences should be used to determine the extent of the microdeletion in the AZF region of infertile men, which is known as 11 extended STSs. By applying mPCR, the authors develop an optimal detection procedure for the 6 basic STS and 11 extended STS using 3 multiplex PCR reactions. The first multiplex PCR reaction includes 6 basic STS plus the 2 control sequences sex-determining region Y (SRY) and zinc finger protein X/Y-linked (ZFX/Y). The second multiplex PCR reaction includes the 6 extended STS sY88, sY1182, sY105, sY121, sY1191, and sY1291 and the 2 control sequences SRY and ZFX/Y. The third multiplex PCR reaction includes the 5 extended STS sY153, sY160, sY82, sY143, and sY83 and the 2 control sequences SRY and ZFX/Y. Six basic primer sequences and eleven extended primer sequences are redesigned to simultaneously pair and amplify STS in the same multiplex reaction: set of 8 primers for 6 basic STS: 6 basic STS + 2 (SRY, ZFX/Y), 8 extension primers set E1: 6 extended STS + 2 (SRY, ZFX/Y), and 7 extension primers set E2: 5 extended STS + 2 (SRY, ZFX/Y). We successfully designed primer pairs with high specificity and stability and successfully amplified 6 basic STS and 11 extended STS, which ensures that the STSs have the correct sequence as recommended by EAA/EMQN and are consistent with the NCBI gene bank. This study has successfully developed a procedure to simultaneously detect 17 STSs, including 6 basic STSs and 11 extended STSs in the AZF region using 3 multiplex PCR reactions.